Effect of heat treatment temperature on microstructure and properties of new maraging stainless steel - WANG Fei-yun; JIN Jian-jun; JIANG Zhi-hua; WANG Xiao-zhen; HU Chun-wen (Cailiao gongcheng, 2019)
The mechanical properties and microstructure of tested steel strengthened via Al at different solution and aging temperatures were studied by mechanical property test, optical microscope and transmission electron microscope. The results show that the tensile strength and yield strength of tested steel reach up to 1876MPa and 1762MPa respectively, with the higher strength and better match of toughness. Fine lath martensite with high-density dislocations is formed after solution and the precipitation of dispersive NiAl phase from matrix makes the strength greatly improved during the aging. The strength of tested steel decreases rapidly after reaching peak due to the coarsening of particles, namely, overaging phenomenon occurs. The optimum comprehensive mechanical properties of tested steel can be obtained after solution treatment at 820℃, cold treatment at -70℃ and aging treatment at 540℃.